2010
DOI: 10.1055/s-0030-1248072
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Experience With the Effectiveness and Tolerability of Hylan G-F 20 in 1047 Patients With Osteoarthritis of the Knee

Abstract: This retrospective review evaluates the effectiveness and tolerability of hylan G-F 20 for relief of pain due to knee osteoarthritis in a large orthopedic practice over a 5-year period. Prospectively collected data from patients who initiated intra-articular hylan G-F 20 (3 weekly injections) for osteoarthritis knee pain treatment were analyzed. Effi cacy variables included physician visual analogue scale (VAS: 100 mm), and patient rating of pain, mobility, and amount of pain medication taken after treatment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 6 publications
3
43
0
Order By: Relevance
“…Open-label prospective, comparative, and retrospective studies also showed improvement of symptoms of knee OA after treatment with sodium hyaluronate 25,32 and hylan G-F 20 [33][34][35][36][37] . In studies comparing hylan G-F 20 with other knee OA treatments, viscosupplementation was an effective adjunct or alternative therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Open-label prospective, comparative, and retrospective studies also showed improvement of symptoms of knee OA after treatment with sodium hyaluronate 25,32 and hylan G-F 20 [33][34][35][36][37] . In studies comparing hylan G-F 20 with other knee OA treatments, viscosupplementation was an effective adjunct or alternative therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The annual change in WOMAC scores for patients receiving hylan G-F 20 is estimated on the basis of results of randomized controlled trials [15][16][17][18]. The available evidence suggests that the benefit obtained by viscosupplementation with hylan G-F 20 is sustained over time [10][11][12][15][16][17][18][19][20][21][22][23]; in light of this, the WOMAC scores after the first year are assigned randomly taking into account the clinical outcome for the previous years.…”
Section: Simulation Methodologymentioning
confidence: 99%
“…The available evidence suggests that the benefit obtained by viscosupplementation with hylan G-F 20 is sustained over time [10][11][12][15][16][17][18][19][20][21][22][23]; in light of this, the WOMAC scores after the first year are assigned randomly taking into account the clinical outcome for the previous years. The information about score variation is available as reported by Raman et al [24].…”
Section: Simulation Methodologymentioning
confidence: 99%
“…HA is generally considered safe compared to CSs or saline (17,35,(40)(41)(42)52). Furthermore, HA is considered safe also after a previous course of HA injections (35,37,40).…”
Section: Adverse Events and Safetymentioning
confidence: 99%